The Ecofeminism and Implementation at Indonesian Language Learning Class of the Song Lyric Seperti Rahim Ibu by Efek Rumah Kaca Band - Guci, Aldo Ferdianda (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research discusses the form of ecofeminism in the lyrics of songs Seperti Rahim Ibu by the band Efek Rumah Kaca and its implications for Indonesian language learning for class high school. The aim of this research is to describe the ecofeminist values ​​contained in the lyrics of the song